A potential flexible fuel cell with dual-functional hydrogel based on multi-component crosslinked hybrid polyvinyl alcohol. (15th February 2023) - Yang, Yang; Xing, Kai; Yan, Minyue; Zhu, Xun; Ye, Dingding; Chen, Rong; Liao, Qiang
Abstract: The flexible energy supplies are urgently needed considering with the rapid development of portable wearable electronic devices. The fuel cells possess the highest theoretical power density compared with batteries and super-capacitors. However, the flexible and bendable applications are hindered by the inconvenient fuel/electrolyte storage and existence of physical membrane. It is necessary to develop one kind of power sources with a straightforward system and integrated fuel/electrolyte supply-storage system. Herein, a new type of hydrogel based on polyvinyl alcohol-polyvinyl pyrrolidone-sulfosuccinic acid semi-interpenetrating network, is synthesized and applied by doping and blending various functional groups. The hydrogel possess the characteristics of high swelling ratio, superior ionic conductivity, good mechanical properties and integrated dual functions. The flexible fuel cell integrated with fuel storage/supply hydrogel is assembled without any external auxiliary system. It delivers a maximum power density of 2.83 mW cm −2 and operates normally under various flexible situations such as bending, twisting, fatigue bending and needling states. Both high flexibility and stability of the hydrogel-based micro fuel cells have been demonstrated upon the wearable and bendable applications. The work illustrates a pathway for designing power sources for flexible electronics with integrated fuel/electrolyte storage and matched mechanical properties. Highlights: Polyvinyl alcohol hydrogel is successfully synthesized by blending polyvinyl pyrrolidone and sulfosuccinic acid. It serves as both fuel/electrolyte storage and ion conductor with good flexibility. The flexible fuel cell operates normally under flexible environment and deliver a high power density.